Application of complex instrumental techniques, spectroscopy and chromatography, for the analysis of biofuels and biomass - Tomić, Tatjana, inženjerka kemijske tehnologije (Array, 2019)
Biofuels are environmentally friendly alternative fuels produced from animal and plant raw materials. They have great significance due to limited availability of crude oil and increased ecological requirements. The development of biofuels is followed by the development of new and more efficient analytical procedures for monitoring the composition and physical-chemical properties. This paper presents the application of chromatographic and spectroscopic methods in the analysis of different types of biofuels. The results of the determination of the hydrocarbon composition and functional groups important for the application of biofuels as blending components are shown. In this paper, it has confirmed the possibility of using NMR spectroscopy, HPLC and IC chromatography in biofuel and biomass analysis.